2020
DOI: 10.3390/ani10071193
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Rumen Bacterial Community and Metabolome Characteristics of Cashmere Goats in Response to Dietary Nutrient Density

Abstract: This study was conducted to investigate the impacts of dietary energy and protein on rumen bacterial composition and ruminal metabolites. A total of 12 ruminal samples were collected from Shaanbei white cashmere goats which were divided into two groups, including high-energy and high-protein (Group H; crude protein, CP: 9.37% in dry matter; metabolic energy, ME: 9.24 MJ/kg) and control (Group C; CP: 8.73%; ME: 8.60 MJ/kg) groups. Thereby, 16S rRNA gene sequencing and a quantitative polymerase chain reaction we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…Similar to previous studies ( 10 , 35 ), Bacteroidetes and Firmicutes were the dominant bacterial phyla, and Neocallimastigomycota and Ascomycota were the dominant fungal phyla—both being important for the degradation and fermentation of diet biopolymers. At the genus level, we found that Prevotella_1 was the dominant bacteria, consistent with previous reports for cashmere goats ( 36 ) and Holstein cattle ( 37 , 38 ). Prevotella_1 plays an important role in the degradation and utilisation of proteins, peptides, starch, hemicellulose, and pectin ( 39 ).…”
Section: Discussionsupporting
confidence: 92%
“…Similar to previous studies ( 10 , 35 ), Bacteroidetes and Firmicutes were the dominant bacterial phyla, and Neocallimastigomycota and Ascomycota were the dominant fungal phyla—both being important for the degradation and fermentation of diet biopolymers. At the genus level, we found that Prevotella_1 was the dominant bacteria, consistent with previous reports for cashmere goats ( 36 ) and Holstein cattle ( 37 , 38 ). Prevotella_1 plays an important role in the degradation and utilisation of proteins, peptides, starch, hemicellulose, and pectin ( 39 ).…”
Section: Discussionsupporting
confidence: 92%
“…High-energy diets increase the relative abundance of Bacteroidetes and Prevotella but reduce the abundance of Proteobacteria. By affecting the bacterial community structure, it alters the synthesis of main metabolites important to animal health [ 14 ]. Despite such important findings, little is known about how a high-energy diet that promotes a weight gain of more than 200 g influences rumen fermentation and microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Peptides have been found to improve microbial protein yield and rumen fermentation ability [ 17 , 18 , 19 ]. Rather than amino acids or ammonia, rumen bacteria can utilize nitrogen from peptides [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%